2014
DOI: 10.1097/won.0000000000000057
|View full text |Cite
|
Sign up to set email alerts
|

Smoking, Chronic Wound Healing, and Implications for Evidence-Based Practice

Abstract: Chronic wounds are rising in prevalence and creating significant socioeconomic burdens for patients and healthcare systems worldwide. Therefore, it is now more important than ever that clinicians follow evidence-based guidelines for wound care when developing personalized treatment plans for their patients with chronic wounds. Evidence-based guidelines for treating venous leg ulcers, diabetic foot ulcers, and pressure ulcers, the 3 main categories of chronic wounds, focus primarily on biologic therapies. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
90
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(93 citation statements)
references
References 61 publications
2
90
0
1
Order By: Relevance
“…Além disso, a nicotina, que representa o principal componente do cigarro, dificulta o transporte do oxigênio nas hemácias, agravando o quadro de hipóxia tecidual. A redução de oxigênio local, além de prejudicar a neoangiogênese e a multiplicação de fibroblastos nas feridas, propicia microambiente favorável para o crescimento de bactérias, aumentando o risco de infecção (20) .…”
Section: Discussionunclassified
“…Além disso, a nicotina, que representa o principal componente do cigarro, dificulta o transporte do oxigênio nas hemácias, agravando o quadro de hipóxia tecidual. A redução de oxigênio local, além de prejudicar a neoangiogênese e a multiplicação de fibroblastos nas feridas, propicia microambiente favorável para o crescimento de bactérias, aumentando o risco de infecção (20) .…”
Section: Discussionunclassified
“…19 However, this lifestyle negatively influences health, and smokers are more susceptible to develop diseases. 19 Several studies show that this addiction harms wound healing and causes problems in skeletal tissues, [19][20][21][22] which represents a high potential risk factor and reduces dramatically the rate of implant success. 21 Twito et al 22 found that the rate of implant failure was higher in the group of smokers than in the group of nonsmokers, when assessing 7,608 implants.…”
Section: Discussionmentioning
confidence: 99%
“…This habit compromises healing and tissue repair due to the vasoconstrictor effect of nicotine, leading to tissue hypoxia, which hinders osseointegration and consequently implant success. 20 Hence, implant survival becomes difficult. 22 Dental implants and implant-supported prostheses are options often used for the rehabilitation of elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…As well, smoking has well known serious complications like carcinogenic effect and lead to the development of cardiovascular and chronic obstructive pulmonary disease [2]. Moreover, it results in a disturbed microcirculation and consequent delayed wound healing [3].…”
Section: Introductionmentioning
confidence: 99%